HucMSC‐exosomes carrying miR‐326 inhibit neddylation to relieve inflammatory bowel disease in mice. Issue 2 (21st June 2020) - Wang, Gaoying; Yuan, Jintao; Cai, Xiu; Xu, Zhiwei; Wang, Jingyan; Ocansey, Dickson K.W.; Yan, Yongmin; Qian, Hui; Zhang, Xu; Xu, Wenrong; Mao, Fei
Abstract: Background: Inflammatory bowel disease (IBD) is a group of chronic intestinal inflammation that is a risk factor for many gastrointestinal cancers. Exosomes are gradually gaining attention as an emerging treatment method for IBD due to their important biological characteristics. NF‐κB is an important pro‐inflammatory transcription factor kept inactive by IκB protein in the cytoplasm by masking the nuclear localization signal of NF‐κB. The deterioration of IκB is mainly ubiquitination, and this depends on neddylation. Methods: In this study, we established a dextran sulfate sodium (DSS)‐induced IBD model in BABL/C mice to evaluate the effect of human umbilical cord mesenchymal stem cell‐derived exosomes (hucMSC‐exosomes, hucMSC‐Ex) on the repair of IBD. At the same time, human colorectal mucosa cells (FHC) were stimulated by LPS (lipopolysaccharide) in vitro to activate the inflammatory environment to study the mechanism of hucMSC‐Ex regulating neddylation. The microRNA (miRNA) obtained by sequencing and transfection with hucMSC‐Ex was used to verify the role of miR‐326/neddylation/IκB/NF‐κB signaling pathway in IBD repair. Results: HucMSC‐Ex inhibited the process of neddylation in relieving DSS‐induced IBD in mice. The binding of NEDD8 (neural precursor cell‐expressed, developmentally downregulated gene 8) to cullin 1 and the activation of NF‐κB signaling pathway were suppressed along with reduced expression levels of neddylation‐related enzyme molecules. The same phenomenon was observed in FHC cells. The miRNA comparison results showed that miR‐326 was highly expressed in hucMSC‐Ex and played an important role in inhibiting the neddylation process. The therapeutic effect of hucMSC‐Ex with high expression of miR‐326 on IBD mice was significantly stronger than that of ordinary hucMSC‐Ex. Conclusions: HucMSC‐Ex relieves DSS‐induced IBD in a mouse model by inhibiting neddylation through miR‐326. Abstract : HucMSC‐Ex carrying miR‐326 relieves intestinal inflammatory damage by inhibiting neddylation within the intestinal mucosal cells. A, HucMSC‐Ex contains multiple active substances, of which miR‐326 is highly expressed. B, miR‐326 targets NEDD8 and inhibits the binding of cullin 1 and NEDD8 (the neddylation of cullin 1), thereby preventing the degradation of IκB; NF‐κB is masked, and the activation of its signaling pathway is suppressed to alleviate inflammation.